2011
DOI: 10.1097/naq.0b013e31820320ff
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Evidence-Based Practice to Improve Nurse and Cost Outcomes in a Community Health Setting

Abstract: Although evidence-based practice (EBP) improves health care quality, decreases costs, and empowers nurses, there is a paucity of intervention studies designed to test models of how to enhance nurses' use of EBP. Therefore, the specific aim of this study was to determine the preliminary effects of implementing the Advancing Research and Clinical practice through close Collaboration (ARCC) model on nurses' EBP beliefs, EBP implementation behaviors, group cohesion, productivity, job satisfaction, and attrition/tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 25 publications
3
51
1
2
Order By: Relevance
“…This study findings also support the practical benefits of the partnership among academia and other institutions, in which expertise and resources are pooled to facilitate EBP adoption across multiple institutions in the region (Gawlinski & Becker, 2012;Granger et al, 2012;Weeks et al, 2011). Similar study findings were previously reported from an educational program in which EBP beliefs and EBP implementation were improved (Abdullah et al, 2014;Levin, Fineout-Overholt, Melnyk, Barnes, & Vetter, 2011), although another EBP educational program based on the ARCC model showed no statistically significant improvements in EBP beliefs and EBP implementation (Underhill, Roper, Siefert, Boucher, & Berry, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…This study findings also support the practical benefits of the partnership among academia and other institutions, in which expertise and resources are pooled to facilitate EBP adoption across multiple institutions in the region (Gawlinski & Becker, 2012;Granger et al, 2012;Weeks et al, 2011). Similar study findings were previously reported from an educational program in which EBP beliefs and EBP implementation were improved (Abdullah et al, 2014;Levin, Fineout-Overholt, Melnyk, Barnes, & Vetter, 2011), although another EBP educational program based on the ARCC model showed no statistically significant improvements in EBP beliefs and EBP implementation (Underhill, Roper, Siefert, Boucher, & Berry, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…The first occurrence was nurses in the intervention group, who began this study with weaker EBP beliefs reported stronger EBP beliefs post-intervention. These results are consistent with other studies that used the EBPB scale pre-and post-intervention and found EBP beliefs can increase with educational interventions [64][65][66]. The second occurrence was nurses in the attention control group, who began this study with stronger EBP beliefs than the intervention group, experienced a substantial decrease in their EBP beliefs postintervention.…”
Section: Ebp Beliefssupporting
confidence: 81%
“…The second occurrence was nurses in the attention control group, who began this study with stronger EBP beliefs than the intervention group, experienced a substantial decrease in their EBP beliefs postintervention. These findings were similar to a pilot study conducted to evaluate the preliminary effects of implementing an EBP model on several variables (i.e., ARCC model) [64]. The authors provided no explanation about this decline in their article.…”
Section: Ebp Beliefssupporting
confidence: 70%
“…Some mentors were physicians nominated by their peers (Berner et al., 2003; Lomas et al., 1991; Soumerai et al., 1998). Other mentors were nurses or other healthcare professionals selected to support nurses (Johnston et al., 2007; Levin, Fineout-Overholt, Melnyk, Barnes, & Vetter, 2011; Mariano et al., 2009; Masny, Ropka, Peterson, Fetzer, & Daly, 2008; Wallen et al., 2010). Only Johnston and colleagues (2007) discussed the mentor selection process, indicating key leaders were selected as mentors.…”
Section: Resultsmentioning
confidence: 99%